1999
DOI: 10.1677/joe.0.1600297
|View full text |Cite
|
Sign up to set email alerts
|

Molecular forms of circulating adrenomedullin in patients with congestive heart failure

Abstract: In the biosynthesis of adrenomedullin (AM), an intermediate form, AM(1-52)-glycine-COOH (iAM), is cleaved from proAM and subsequently processed to a biologically active mature form, AM(1-52)-NH 2 (mAM), by enzymatic amidation. We recently reported that immunoreactive AM in human plasma consists of mAM and iAM. To clarify the pathophysiological roles of mAM and iAM in heart failure, we established an assay method to specifically detect mAM, and we determined the plasma concentrations of mAM and iAM in 68 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 22 publications
5
38
1
1
Order By: Relevance
“…These same workers demonstrated an increase in both intermediate form (inactive) glycine-extended adrenomedullin and the amidated mature form of adrenomedullin, and whereas both increase according to the severity of heart failure (New York Heart Association (NYHA) functional class), the ratio of mature to total (mature plus intermediate form) adrenomedullin remains similar to that in controls (10). They have further shown that effective treatment of heart failure gradually results in a reduction in circulating levels of adrenomedullin (10,11). In addition, they have reported that pericardial fluid adrenomedullin immunoreactivity is increased slightly compared with plasma, but mature adrenomedullin, and the mature/ total adrenomedullin ratios are much higher than in plasma (12).…”
Section: Plasma Adrenomedullin Levels In Heart Failurementioning
confidence: 77%
See 1 more Smart Citation
“…These same workers demonstrated an increase in both intermediate form (inactive) glycine-extended adrenomedullin and the amidated mature form of adrenomedullin, and whereas both increase according to the severity of heart failure (New York Heart Association (NYHA) functional class), the ratio of mature to total (mature plus intermediate form) adrenomedullin remains similar to that in controls (10). They have further shown that effective treatment of heart failure gradually results in a reduction in circulating levels of adrenomedullin (10,11). In addition, they have reported that pericardial fluid adrenomedullin immunoreactivity is increased slightly compared with plasma, but mature adrenomedullin, and the mature/ total adrenomedullin ratios are much higher than in plasma (12).…”
Section: Plasma Adrenomedullin Levels In Heart Failurementioning
confidence: 77%
“…These investigators have noted that immunoreactive adrenomedullin levels increase with the clinical severity of heart failure, and show a positive statistical association with pulmonary artery pressure and pulmonary wedge pressure, an inverse relationship to left ventricular ejection fraction, and positive correlations with neurohormonal indices such as plasma atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP), and renin (7)(8)(9). These same workers demonstrated an increase in both intermediate form (inactive) glycine-extended adrenomedullin and the amidated mature form of adrenomedullin, and whereas both increase according to the severity of heart failure (New York Heart Association (NYHA) functional class), the ratio of mature to total (mature plus intermediate form) adrenomedullin remains similar to that in controls (10). They have further shown that effective treatment of heart failure gradually results in a reduction in circulating levels of adrenomedullin (10,11).…”
Section: Plasma Adrenomedullin Levels In Heart Failurementioning
confidence: 83%
“…7,49,50 Immunoreactive AM in plasma or tissues was found to consist of 2 molecular forms, mAM and iAM (Figure 2), with the major molecular type in plasma and tissues being iAM and mAM, respectively. 7,49 -51 As described in the next section, plasma levels of immunoreactive AM were found to be higher in patients with arteriosclerotic vascular diseases than controls, although there was no notable difference in the ratio of mAM and iAM.…”
Section: Circulating Am In the Bloodstreammentioning
confidence: 99%
“…On the other hand, recent studies revealed that two molecular forms of AM circulate in human plasma, and the major circulating form is the inactive form, AM-glycine (11-13). Hirayama et al reported that both molecular forms of AM are similarly increased in patients with heart failure (14). Thus, AM may respond to the pathophysiology of heart failure and may be a biochemical marker for the severity of heart failure.…”
Section: Plasma Am Levels In Heart Failurementioning
confidence: 99%
“…Regarding the effect of AM on cardiac hypertrophy, Tsuruda et al (35) reported that AM significantly reduced the angiotensin II-and 10% fetal bovine serum-stimulated 14 Cphenylalanine incorporation into cardiac myocytes, and that this inhibitory effect of AM on the stimulated 14 C-phenylalanine incorporation was abolished dose-dependently by an AM receptor antagonist, CGRP(8-37). These results suggest that AM may act on cardiomyocytes as an autocrine or a paracrine anti-growth factor.…”
Section: Cardiac Action Of Ammentioning
confidence: 99%